Challenges at the Beginning of the XX Century for the Albanian Nation, Literature and Culture - Kurti, Ledri (Mediterranean Journal of Social Sciences, 2012)
This study surveyed the facing challenges in the Albanian nation, at the beginning of XX century. As a result challengesaccompanied definitely its shrink literature in suppressed conscience. Time as a concept had nothing to do with the chain of phenomenaaround. Time in itself, in this geographical and historical terrain, and in its literature, could not be in motion, became a painful stagnationdetached from the light and the effects of objective time or the reflections of developments in the whole. Attempts to capture the lost timeand facing with reality, would reasonably be met with the resistance and gears of real time and the difficulties which brought theconfrontation with different mentalities, the general development of other nations, hence the philosophies of thought and theirrepresentative literature of their developments.